2023
DOI: 10.53479/25027
|View full text |Cite
|
Sign up to set email alerts
|

Trust and accountability in times of pandemic

Abstract: The COVID-19 pandemic took place against the backdrop of growing political polarization and distrust in political institutions in many countries. Furthermore, most governments fell short of expectations in their management of the pandemic. Did deficiencies in government performance further erode trust in public institutions? Did citizens’ ideology interfere with the way they processed information on government performance? To investigate these two questions, we conducted a preregistered online experiment in Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…67 Using a high-frequency large-scale online survey, Fancourt, Steptoe and Wright (2020) notice that trust in the government (but not in other dimensions) sharply fell soon after the Cummings episode in England (but not in the other nations belonging to the United Kingdom). The importance of political accountability and trust is also studied by Martinez-Bravo and Sanz (2023) in the Spain. Interestingly, Bird et al (2023) find that, in Latin America, political trust predicted less compliance (more mobility), unlike in high-income countries.…”
Section: The "Cummings E↵ect"mentioning
confidence: 99%
“…67 Using a high-frequency large-scale online survey, Fancourt, Steptoe and Wright (2020) notice that trust in the government (but not in other dimensions) sharply fell soon after the Cummings episode in England (but not in the other nations belonging to the United Kingdom). The importance of political accountability and trust is also studied by Martinez-Bravo and Sanz (2023) in the Spain. Interestingly, Bird et al (2023) find that, in Latin America, political trust predicted less compliance (more mobility), unlike in high-income countries.…”
Section: The "Cummings E↵ect"mentioning
confidence: 99%
“…Some of these findings also highlighted that satisfaction with governmental responses, together with the need for unity and political stability, emerged as the main factors that influenced political trust during the pandemic 48 . Other studies documented that the positive perception of the government's response to the pandemic was key to sustain high levels of political trust [49][50][51] . In particular, Martinez-Bravo and Sanz 50 showed that priming individuals with negative cues on regional pandemic management policies affected political trust.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies documented that the positive perception of the government's response to the pandemic was key to sustain high levels of political trust [49][50][51] . In particular, Martinez-Bravo and Sanz 50 showed that priming individuals with negative cues on regional pandemic management policies affected political trust.…”
Section: Introductionmentioning
confidence: 99%
“…The specific literature on institutional trust in the context of the COVID-19 pandemic has focused on the role of trust for behaviors and outcomes at the individual and group levels (Brodeur et al 2021;Sarracino et al 2021;Martinez-Bravo and Sanz 2022;Suhay et al 2022;Fanny Lalot et al 2022;Schomaker et al 2020;Jäckle et al 2023;Woelfert and Kunst 2020). Existing studies considering countermeasures have focused on trust as a mediator or moderator variable, primarily for prosocial behaviors, health outcomes and pandemic management (Bargain and Aminjonov 2020;O'Hara et al 2020;Pak et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies into the impact of policy restrictions have focused on economic impacts of hard lockdowns, including employment and growth (Demirgüç-Kunt et al 2021;König and Winkler 2021;Kok 2020;Ueda et al 2021), food prices (Akter 2020) and stock markets (Aggarwal et al 2021;Yang and Deng 2021;Ashraf 2020;Kizys et al 2021). Another body of work has studied compliance with hard lockdown measures, such as stay-at-home measures, including the role of trust, which appear to play a key role for acceptance and compliance of policies (Bargain and Aminjonov 2020;Brodeur et al 2021;Pak et al 2021;Sarracino et al 2021;Martinez-Bravo and Sanz 2022;Suhay et al 2022;Fanny Lalot et al 2022;Schomaker et al 2020;Jäckle et al 2023;Woelfert and Kunst 2020). These studies mainly found higher compliance when individuals trust in institutions (see e.g.…”
mentioning
confidence: 99%